Organic Catfish Feed From Cow Manure - Widyastuti, Sri; Rosyid , Dimas Muhammad (Tibuana, 2020)
Artificial feeding feeding is given asadditional feed to accelerate the process of fishenlargement. Self-processing of feed can beconducted by utilizing cow manure through thefermentation process and the addition of aneffective microorganism (EM4) solution. Thisresearch used 3 treatments which arefermentation for 5, 9, 11 days with each drycow manure of 2 kg with water content of 19%.The resulting feed was then tested for qualityto determine protein and fat content. The 3treatments produced levels of nutrient proteinand fat as follows: protein levels in treatment I(6.16%), II (7.57%), III (7.68%) while the fatcontent in treatment I (0.15 %), II (0.50%), III(0.60%). The results of feed from alltreatments were given to catfish. Catfishgrowth was observed for 10 days. Weight gainfrom the initial weight of 400 gr, on treatment1 to the 10th day: 500 grams, the secondtreatment to the 10th day weighing 600 grams,treatment 3 to the 10th day: 1000 grams.Resulted feed haven’t met Quality Standardsfor SNI Feed No SNI: 01-4087-2006.